Analysis of the Influence of Career Development on Employee Performance at the Development Planning and Regional Development Research Agency of Batu Bara Regency - Alfandy M. Harahap; Muhammad Iqbal; Ferdinan Juliaman Simangunsong; Eppi Sumanti; Muhammad Bob Widiansyah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of career development, reward system, and organizational culture on employee performance at the Regional Development Planning and Development Research Agency of Batu Bara Regency, focusing on the effect of career development. The research method uses a quantitative approach with a sample of 30 employees selected purposively. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that partially, career development has no significant effect on employee performance (t count 1.358 < t table 2.055; sig. 0.185 > 0.05). Conversely, the reward system and organizational culture have a positive and significant partial effect. However, simultaneously, these three variables have a positive and significant effect on employee performance, with an F count of 12.950 > F table 2.98. This finding indicates that the existing career development program is not yet optimal and has not been able to independently drive performance improvement, so it needs to be evaluated and integrated with the reward system and strengthening organizational culture to achieve better employee performance.